Ana's Story : A Journey of Hope - Bush, Jenna; Baxter, Mia. (New York, NY : HarperCollins Publishers, 2007)
The author reveals the life of a young woman she met while on an internship with UNICEF and how, despite living with HIV and losing her family to AIDS, she is thriving and looking forward to giving her child a better life.
Keywords: AIDS (Disease) -- Patients